1998
DOI: 10.1093/ageing/27.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Can bedside assessment reliably exclude aspiration following acute stroke?

Abstract: Bedside assessment of swallowing lacks the necessary sensitivity to be used as a screening instrument in acute stroke, but there are concerns about the use of videofluoroscopy as a gold standard. The relative importance of aspiration and bedside assessment in predicting complications and outcome needs to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
1
23

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(181 citation statements)
references
References 16 publications
6
151
1
23
Order By: Relevance
“…These data are consistent with the poor inter-and intra-reliability of the BSE in patients suffering from an acute stroke [23]. While the operating characteristics of the BSE have not been studied in recently-extubated survivors of critical illness, several studies of other patient groups have suggested limited diagnostic accuracy when compared to gold standard tests [15,[24][25][26].…”
Section: Discussionsupporting
confidence: 65%
“…These data are consistent with the poor inter-and intra-reliability of the BSE in patients suffering from an acute stroke [23]. While the operating characteristics of the BSE have not been studied in recently-extubated survivors of critical illness, several studies of other patient groups have suggested limited diagnostic accuracy when compared to gold standard tests [15,[24][25][26].…”
Section: Discussionsupporting
confidence: 65%
“…Os níveis de alerta, colaboração e atenção já demonstraram sua importância na avaliação da deglutição, especialmente de pacientes com acometimento neurológico (Smithard et al, 1998;Logeman et al, 1999;Trapl et al, 2007;Padovani et al, 2008;Masiero et al, 2008;Leder et al, 2009). …”
Section: Redução Do Alerta Não Colaborativo E/ou Desatentounclassified
“…Investiga-se a necessidade de estimulação (tátil ou verbal) para manter-se alerta; se o paciente adormece, tem fechamento ocular ou flutuação de sonolência durante a avaliação; permanece constantemente ou parcialmente agitado; recusa-se a completar as tarefas ou aceitar o alimento oferecido; necessita de repetição de pistas para fazer ou completar tarefas; não mantém contato de olho com o examinador e/ou fala incessantemente sem focalizar a atenção para a alimentação (Smithard et al, 1998;Logeman et al, 1999;Mullen, 2004;Trapl et al, 2007;Leder et al, 2009). …”
Section: Redução Do Alerta Não Colaborativo E/ou Desatentounclassified
See 1 more Smart Citation
“…Como exemplo ressalta-se a importância da língua na fala, na preparação e na retropropulsão do bolo alimentar. Barer (1989) Se o resultado da sensitividade do instrumento de avaliação for suficientemente preciso para permitir seu uso na rotina, possibilitará a identificação dos pacientes que não apresentam riscos de aspiração pela equipe médica ou de enfermagem e apenas os que apresentarem estes riscos permanecerão restritos a dieta zero por via oral (SMITHARD et al, 1998). Os fatores chaves para o manejo da disfagia são o diagnóstico e a intervenção precoce (HORNER et al, 1991).…”
Section: Análise Dos Dadosunclassified